Effectiveness of XP-Endo Finisher and passive ultrasonic irrigation on intracanal medicament removal from root canals: a systematic review and meta-analysis - Jiani Zhou; Tingjun Liu; Lihong Guo (BMC, 2021)
Abstract Background XP-Endo Finisher (XPF) and passive ultrasonic irrigation (PUI) are commonly used in intracanal medicament removal. The effectiveness of these two techniques needs to be compared, and evidence-based research should be conducted. Methods A comprehensive literature search was conducted in PubMed, Web of Science, Embase, Cochrane Library, and Google Scholar up to December 20th, 2020. The outcomes of the included trials were pooled into the Cochrane Collaboration's Review Manager 5.3 software. Cochrane's risk-of-bias tool 2.0 was applied to assess the risk of bias. Results Nine articles were included in this systematic review and processed for data extraction, and eight studies were identified for meta-analysis. In general, the use of PUI showed better medicament removal effectiveness than XPF (odds ratio [OR]: 3.09; 95% confidence interval [CI], 1.96-4.86; P < 0.001). PUI was also significantly more efficient than XPF in the apical third (OR: 3.42; 95% CI, 1.32-8.84; P = 0.01). For trials using sodium hypochlorite (NaOCl) alone, PUI was also significantly more effective than XPF on intracanal medicaments removal (OR: 5.23; 95% CI, 2.79-9.82; P < 0.001). However, there was no significant difference between PUI and XPF when NaOCl and ethylenediaminetetraacetic acid (EDTA) were used in combination (OR: 1.51; 95% CI, 0.74-3.09; P = 0.26). In addition, for studies whose intracanal medicament periods were two weeks, the effectiveness of PUI was statistically better than the XPF (OR: 7.73; 95% CI, 3.71-16.07; P < 0.001). Nevertheless, for trials whose intracanal medicament time was one week or over two weeks, no differences between the XPF and PUI were found (OR: 1.54; 95% CI, 0.74-3.22; P = 0.25) (OR: 1.42; 95% CI, 0.44-4.61; P = 0.56). Conclusions The meta-analysis is the first study to quantitatively compare the effectiveness of XPF and PUI techniques on intracanal medicaments removal. With rigorous eligibility criteria, the study only included high-quality randomised controlled trials. The study indicated that PUI might be superior over XPF techniques for removing intracanal medicaments from artificial standardized grooves and cavities in the root canal system. The anatomical areas, irrigation protocol, and intracanal medicaments time may influence the cleaning efficacy.